Spinal cord stimulation to achieve wound healing in a primary lower limb critical ischaemia referral centre. Issue 2 (8th April 2014) - De Caridi, Giovanni; Massara, Mafalda; David, Antonio; Giardina, Massimiliano; La Spada, Michele; Stilo, Francesco; Spinelli, Francesco; Grande, Raffaele; Butrico, Lucia; de Franciscis, Stefano; Serra, Raffaele
Abstract: Critical lower limb ischaemia is a diffuse pathology that could cause claudication, severe ischaemic pain and tissue loss. The common treatment includes modification of risk factors, pharmacological therapy and endovascular or surgical revascularisation of the lower limb to restore a pulsatile flow distally. Spinal cord stimulator is seen as a valid alternative in patients unsuitable for revascularisation after endovascular or surgical revascularisation failure and as adjuvant therapy in the presence of a functioning bypass in patients with extensive tissue loss and gangrene presenting a slow and difficult wound healing. We report our experience on spinal cord stimulation (SCS) indication and implantation in patients with critical lower limb ischaemia, at a high‐volume centre for the treatment of peripheral arterial disease.